(*The manuscript was retracted due to double publication*) - Editor, Editor (Journal of Applied Studies in Language, 2019)
Manuscript on pages 1 to 9 published in this journal is retracted or deleted because the same manuscript was submitted and published in another online journal. Withdrawal of manuscripts also upon request and notification from the script author (Editor of JASL). September 29, 2019, at 6:25 PM,  an email was sent to the Editor of the Journal of Applied Studies in Language (shortened into JASL). This was about an inquiry of one of the authors of a manuscript or research article published by JASL, in which I am a chief editor of the journal, in order to withdraw the author's manuscript. A prompt reply was sent as a response to the inquiry that the withdrawal will be executed after another manuscript was sent to substitute the manuscript was published in June 2019. The author informed the editor since the same manuscript was published in another journal. The author promised to write another manuscript as a replacement for the previous manuscript, but unfortunately, the long-awaited manuscript did not arrive and was received by the journal editor until finally, the manuscript had to undergo a manuscript withdrawal process from the journal publication.